Tingkat Ketergantungan Keuangan Daerah - Abdullah, Julie; Hasan, Wahyudin (Gorontalo Accounting Journal, 2022)
The purpose of writing this article is to determine the level of regional financial dependence in the North Bolaang Mongondow Regency using the method of financial ratio analysis. Â The results showed that over 5 years the government of North Bolaang Mongondow Regency relied heavily on transfer funds from external parties to finance regional expenditures with an average percentage of financial dependence of 93.29 percent. Â This high percentage rate shows that the contribution of local original income to the total regional income of the North Bolaang Mongondow Regency is still minimal.